ACCULTURATION OF RELIGION AND TRADITION IN MAUDU’ LOMPOA - Harry Yulianto (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2023)
The culture resulted from hybridization and traditional complexity between global and local phenomena. Culture can be changed and acculturation with other cultures, so the culture was seen as dynamic. One Indonesian culture that still survives today was a tradition to celebrate the birthday of Prophet Muhammad SAW. Although, over the years, the tradition has experienced a slight shift in line with the times, it is still celebrated regularly every year by most Muslims, one of them in Takalar; it has called Maudu' Lompoa. This study uses qualitative methods and data analysis methods using descriptive qualitative data analysis techniques. The study's purpose is to describe the historical meaning contained in the tradition of Maudu' Lompoa. The results indicate there is acculturation between religion and tradition in Maudu' Lompoa.